Utilization of Citronella Oil as an Anti-dandruff (Candida Albicans) Shampoo Formulation - Zya Rizqina Musfa Rizqina; Nurmahni Harahap (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
Shampoo is a liquid that increases tension on the surface of the scalp so that it can clean dirt from the hair and scalp. Each shampoo should have its own formula to clean dirt from the scalp because each formula contains different ingredients. It is not uncommon to find shampoos that use natural ingredients in their formula. The natural ingredient used in this study is lemongrass oil. Lemongrass oil is one of Indonesia's commercial essential oils obtained through distillation. Lemongrass oil has many benefits for the hair and scalp. The purpose of this study was to determine how to make anti-dandruff shampoo using a lemongrass oil formula. The method used in this research is the experimental method. The subjects of this study were 10 students and 1 teacher of MTsN 1 Model Banda Aceh. Therefore, this shampoo is proven to strongly inhibit the growth of the Candida albicans fungus, also known as dandruff. In addition, the panelists also explained that using this shampoo felt comfortable because of its soft and foamy texture.